2019
DOI: 10.1021/acs.chemrestox.9b00406
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Metals-Mediated Phospholipids Scrambling by Human Phospholipid Scramblase 3: A Probable Role in Mitochondrial Apoptosis

Abstract: Human phospholipid scramblases are a family of four homologous transmembrane proteins (hPLSCR1–4) mediating phospholipids (PLs) translocation in plasma membrane upon Ca2+ activation. hPLSCR3, the only homologue localized to mitochondria, plays a vital role in mitochondrial structure, function, maintenance, and apoptosis. Upon Ca2+ activation, hPLSCR3 mediates PL translocation at the mitochondrial membrane enhancing t-bid-induced cytochrome c release and apoptosis. Mitochondria are important target organelles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Cell research. MeHg similarly to Hg 2+ induces mitochondrial apoptosis and oxidative stress, mediating an increase in ROS production, a decrease in cell antioxidant defense, and cytochrome c release from mitochondria [151,152]. Hg 2+ induced apoptosis with caspase-3 activation, a cell viability decrease, mitochondrial integrity decline, and intracellular ATP depletion.…”
Section: Tl(i) Mitochondrial Researchmentioning
confidence: 99%
“…Cell research. MeHg similarly to Hg 2+ induces mitochondrial apoptosis and oxidative stress, mediating an increase in ROS production, a decrease in cell antioxidant defense, and cytochrome c release from mitochondria [151,152]. Hg 2+ induced apoptosis with caspase-3 activation, a cell viability decrease, mitochondrial integrity decline, and intracellular ATP depletion.…”
Section: Tl(i) Mitochondrial Researchmentioning
confidence: 99%
“…18 Previous studies have shown that changes in mitochondrial integrity affect changes in the ATP content and ATP enzyme activity. 19 Hg 2+ and Pb 2+ cause apoptosis by enabling the mitochondria to produce large amounts of ROS and by releasing cytochrome-C. 20 plays a vital role in glycogen metabolism and cell proliferation and regulation. 21 GSK-3β regulates apoptosis in SH-SY5Y cells.…”
Section: ■ Introductionmentioning
confidence: 99%